Deliberation after Consensus: Introduction to the Symposium - Cathrine Holst; Henrik Friberg-Fernros; Johan Karlsson Schaffer (Journal of Deliberative Democracy)
This editorial introduction presents an overview of the themes explored in the symposium on Deliberation after Consensus. For all the talk of its obsolescence and irrelevance, the concept of consensus still remains centrally contested through generations of deliberative democracy scholarship. In face of criticism for being neither empirically feasible nor normatively desirable, some deliberative theorists have moved away from consensus-oriented teleology and argued in favor of other legitimate outcomes of deliberations. Other theorists have resisted this move, claiming that the aim of deliberation implies that consensus should remain as a regulative ideal for deliberative outcomes. Engaging with these debates about the role of consensus in theories of deliberative democracy, this symposium brings together a selection of innovative, original research articles that raise novel questions about the role consensus could and should play in democratic deliberation and in a deliberative democracy. This introduction offers an overview of the debate over consensus drawing on the notion of successive generations of deliberative democracy research. Our aim is to demonstrate that the view of consensus has changed during generations of deliberative scholarships, but also that some scholars still defend the normative importance of the meaning of consensus once developed by the first generation. Consequently, there are tendencies of both change and continuity in the debate over consensus in deliberative theory. We conclude this introduction by providing a brief synopsis of each paper.